ORGANIZATIONAL CLIMATE AND EMPLOYEE JOB ATTITUDE: A CRITICAL REVIEW OF THE LITERATURE - Maxwell Nwinye (Journal Park Publishing, 2022)
Organizational climate plays a vital role in determining employee job attitudes, predicting their satisfaction, commitment, motivation, and overall performance. A positive organizational climate is characterized with autonomy, organized communication, effective decision making, and supportive leadership to promote higher commitment, job satisfaction, and engagement among employees. However, a negative organizational climate, leads to turnover intention, lack of trust, undecided expectations, decreased morale, disengagement, and poor communication. This study examined organizational climate and employee job attitude in hospitality industry, Rivers State. When companies actively nurture a healthy organizational climate, it creates improve employee job attitudes, leading to enhanced productivity, innovation, and organizational victory. The researcher recommends that hospitality industry should ensure that the employees have autonomy or freedom to use their initiatives in performing their duties, in order to achieve high employee commitment and job satisfaction.
Keywords: Organizational climate, communication, employee commitment, employee job attitude.